2019
DOI: 10.1039/c9ta06506g
|View full text |Cite
|
Sign up to set email alerts
|

Design strategies toward catalytic materials and cathode structures for emerging Li–CO2 batteries

Abstract: The state-of-the-art design strategies toward highly active catalytic materials and cathode structures for Li–CO2 batteries are reviewed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 188 publications
2
56
0
Order By: Relevance
“…Heteroatom doping has been wildly applied to the development of other electrocatalysts for energy conversion reactions. [ 155–158 ] The metal phosphide such as Ni 2 P has been demonstrated to be active catalysts for LiPSs conversion and since it receives a certain degree of cation dopants and disorder in the original crystallographic framework. The Co dopants in Ni 2 P (denoted Ni 2 Co 4 P 3 ) can raise the d‐band structure of metal sites and facilitate the interaction between catalyst and LiPSs, thereby decreasing the activation barrier of LiPSs conversion ( Figure 8 a).…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
“…Heteroatom doping has been wildly applied to the development of other electrocatalysts for energy conversion reactions. [ 155–158 ] The metal phosphide such as Ni 2 P has been demonstrated to be active catalysts for LiPSs conversion and since it receives a certain degree of cation dopants and disorder in the original crystallographic framework. The Co dopants in Ni 2 P (denoted Ni 2 Co 4 P 3 ) can raise the d‐band structure of metal sites and facilitate the interaction between catalyst and LiPSs, thereby decreasing the activation barrier of LiPSs conversion ( Figure 8 a).…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
“…Li 2 O 2 tend to convert to Li 2 CO 3 as a thermodynamically favorable process in presence of CO 2 according to their standard Gibbs free energies of formation. [ 57 ] Several studies have also confirmed the generation of Li 2 CO 3 because of the reaction between Li 2 O 2 , [ 44,58 ] O 2 − , [ 59,60 ] and CO 2 . The Li 2 CO 3 film acting as a passivating layer covers on the surface of cathode, which leads to large interfacial resistance [ 28 ] and impedes the growth of Li 2 O 2 .…”
Section: Cathodementioning
confidence: 99%
“…[ 81,82 ] Noble metals with intrinsic semi‐filled antibonding states can enhance the reaction kinetics through improving the interfacial interaction between different reactants. [ 83,84 ] In the case of Na‐O 2 batteries, various Pt nanoparticles grown on graphene nanosheets, [ 85 ] Ag nanoparticle‐decorated reduced graphene oxide, [ 86 ] micrometer‐sized RuO 2 , [ 87 ] RuO 2 nanoparticles dispersed on carbon nanotubes, [ 88 ] and Pd nanoparticles grown on ZnO‐coated graphitized carbon black [ 89 ] have all been adopted as oxygen cathode. In 2015, Yang’s group synthesized Pt nanoparticles that were in situ grown on graphene nanosheets (Pt@GNSs) through a traditional hydrothermal method as air cathode for the Na‐O 2 battery system.…”
Section: Materials Design Of Air Cathodesmentioning
confidence: 99%